Successful Desensitization of a Patient with Rituximab Hypersensitivity. (20th January 2015) - Ataca, Pinar; Atilla, Erden; Kendir, Resat; Bavbek, Sevim; Ozcan, Muhit
Abstract : Rituximab is a monoclonal antibody which targets CD20 in B cells that is used for the treatment of CD20 positive oncologic and hematologic malignancies. Rituximab causes hypersensitivity reactions during infusions. The delay of treatment or loss of a highly efficient drug can be prevented by rapid drug desensitization method in patients who are allergic to rituximab. We report a low grade B cell non-Hodgkin lymphoma patient with rituximab hypersensitivity successfully treated with rapid drug desensitization. In experienced centers, drug desensitization is a novel modality to break through in case of hypersensitivity that should be considered.